Unveiling the buffering role of prior ties in relationship conflict management in the construction industry - Gan, Xueqing; Le, Yun; Jia, Jianyao; Liu, Tingting; Jiang, Kaiwen; Wei, Xiaokun (Journal of Civil Engineering and Management, 2025)
Relationship conflict is commonplace during the cooperation period between the general contractor and subcontractor. However, how to prevent the adverse effect arising from relationship conflict on the final project outcome is scarce, especially in empirical studies. Drawing on the conservation of resources (COR) theory, a theoretical model revealing the underlying deteriorating mechanism (relational behavior) and corresponding prevention strategies (prior ties) is developed. Based on 174 questionnaires collected from the Chinese construction industry, the model and proposed hypotheses are empirically examined. The results suggest that relationship conflict between the general contractor and subcontractor harms cooperation performance, and relational behavior mediates this relationship. If the general contractor and subcontractor have a prior cooperative relationship, the devasting impact of relationship conflict can be undermined. These findings deepen the understanding of the underlying mechanism by which relationship conflict impairs the final cooperation performance and afford insights into relationship conflict management from a pre-prevention perspective.